Factors that affect speaking skills of students from ethnic minorities in English language learning - Nisrina Nisrina (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2023)
The idea of speaking skills is interconnected with the environment and social context of students poses new challenges by students from ethnic minorities in English language learning. These factors encompass the hindrances and the success of ethnic minority students in adjusting themselves in speaking classes. From 95 first-year students in English Language Teaching program, 18 of them have different minor ethnicities. This study adopted a qualitative study by using semi-structured interviews as an instrument of research. The data then transcribed, coded, and analyzed into different themes that are in line with the research objectives. The results of this study show that the difficulties experienced by students from ethnic minorities in adjusting themselves in speaking classes are the lack of confidence, shyness, and anxiety, speaking opportunities and vocabulary masteries, feeling isolated, and additive bilingualism from peers. However, these hindrances can be solved by various factors: teachers’ decision in designing discussed topics and speaking activities in classroom setting.Keywords: ethnic minority students; speaking class; hindrances; encouragementFaktor-faktor yang mempengaruhi kemampuan berbicara siswa etnis minoritas dalam pembelajaran bahasa InggrisPemikiran bahwa kemampuan berbicara sangat erat berkaitan dengan lingkungan dan konteks sosial siswa menjadikan tantangan tersendiri bagi siswa etnis minoritas dalam pembelajaran Bahasa Inggris. Faktor-faktor ini mencakup kendala dan keberhasilan siswa ethis minoritas dalam menyesuaikan diri di kelas berbicara. Dari 95 siswa yang berada di semester pertama program Pendidikan Bahasa Inggris, 18 diantaranya berasal dari etnis minoritas yang beragam. Penelitian ini mengadopsi desain kualitatif dengan menggunakan wawancara semi terstruktur sebagai instrumen. Data ditranskrip, dikodekan dan dianalisis kedalam beberapa tema sesuai dengan fokus penelitian. Hasil penelitian menunjukkan bahwa kesulitan yang dialami siswa etnis minoritas dalam beradaptasi di kelas berbicara diantaranya rasa percaya diri, malu dan cemas, pengalaman berbicara dan perbendaharaan kata, perasaan terisolasi dan aditif bilingualism dari teman. Namun, kendala tersebut berangsur-angsur dapat diatasi karena faktor: pilihan dosen terhadap topik yang didiskusikan dan kegiatan aktifitas pada kelas berbicara.Kata kunci: siswa etnis minoritas; kelas berbicara; kendala; pendukung